Optimalisasi Pola Asuh Anak di Era Digital Melalui Edukasi Parenting di Desa Dukuhturi, Kecamatan Bumiayu, Kab. Brebes - Aulia, Safanah; Edi Laksono, Gangsar; Nariswari Halisya Putri, Naila; Mubarokah, Iin (Cahaya Smart Nusantara, 2025)
Parenting in the digital age presents new challenges for parents, especially in rural areas such as Dukuhturi Village. The rapid development of technology affects various aspects of life, including how to educate and care for children. This research aims to optimize parenting through parenting education using the Asset-Based Community Development (ABCD) method. The ABCD method focuses on utilizing existing assets and potential within the community to develop educational programs that suit local needs. Parenting education in Dukuhturi Village was conducted by involving various parties, including community leaders, pregnant women, parents, PKK mothers and social service cadres, in order to create an environment that supports healthy and balanced child development in the digital era. The results showed that the ABCD approach is effective in strengthening the capacity of parents in facing parenting challenges in the digital era, as well as increasing community awareness of the importance of their active role in the parenting process.